The Composition, Structure, and Standing Carbon Stock of Teak Based Agroforestry Systems in Gundih, Grobogan Regency, Central Java - Annisa Katleya Isnaini; Santhyami Santhyami (Jurnal Ilmu Lingkungan, 2024)
The teak-based agroforestry system in Gundih, Grobogan Regency, Central Java Province is potentially equivalent to a secondary forest, based on the biodiversity, carbon stock, and utility. This study is prompted by the lack of research on tree vegetation analysis in teak-based agroforestry systems. The aim of this study is to determine the composition and structure of tree vegetation in agroforestry systems within the Gundih area. The research method used plots measuring 20 x 20 m2, in a sampling area of 1 ha and with plot placement using the Purposive Sampling method. The results show that there are 12 tree species from 9 families with a total population of 341 trees/ha. The two tree species with the highest Important Value (IV) are Tectona grandis L.f (93,48) and Swietenia mahagoni (L.) Jacq (66,78). The tree diversity of teak-based agroforestry systems is classified as moderate with an H’ value of 1,81. The carbon stock of tree stands in the agroforestry system is 64,43 MgC/ha. It can be concluded that teak-based agroforestry has the potential to be an option for environmental conservation.